THE DEVELOPMENT OF MEDIA IN PUBLIC RELATIONS OF RESEARCH RESULTSTHROUGH SOCIAL MEDIA VIA FACEBOOK - Wannakayont, Asada; Lonkunthos, Nikom; Dumnil, Suchat; Praisin, Aphichai (Journal of MCU Nakhondhat, 2022)
The research objectives were to develop media and access the satisfaction on media in public relations of research results through social media via Facebook. It's Research and Development. The participants were 70 visitors from the Facebook of the Ph.D. program in the discipline of Industrial Technology by using accidental sampling or convenience selection. The research tools consisted of, the research media and an online satisfaction assessment form. Developed media in public relations of the research by applying the principle of media development (ADDIE Model). After that, post by writing the messages and insert the media into the PhD Facebook Fan Page. By using 120 days for publication to collect data. The participants have to watch, participate, and complete the satisfaction assessment. The descriptive statistics used for analysis include Percentage (%), Mean ( ), and Standard Deviation (S.D) The research results found that 1) there are the media in research public relations used by program Instructors to present the research results through social media via Facebook, which could access widely to the target group and interested people, and public knowledge of the research finding applicable. Make the program gain credibility, good image creation and acceptable in academics. 2) Most of the answerers are 48 males (68.57%), 35 people (50%) in the range of age 15-25 years old, 44 people (62.86%) with bachelor’s degree Graduation, and there are 35 students (50%). The overall satisfaction with media in public relations of research results was at the highest level ( = 4.81, S.D.= 0.42)